TouchWave: Kinetic Multi-touch Manipulation for Hierarchical Stacked Graphs - Baur, Dominikus; Lee, Bongshin; Carpendale, Sheelagh (Proceedings of ITS 2012, 2012)
The increasing popularity of touch-based devices is driving us to rethink existing interfaces. Within this opportunity, the complexity of information visualizations offers particular challenges. We explore these challenges to bring multi-touch interactions to a specific visualization technique, stacked graphs. Stacked graphs are a visually appealing and popular method for presenting time series data, however, they come with associated problems—issues with legibility, difficulties with comparisons, and restrictions in scalability. We present TouchWave, a rethinking and extension of stacked graphs for multi-touch capable devices that provides a variety of flexible layout adjustments, interactive options for querying data values, and seamlessly switching between different visualizations. In addition to ameliorating the main issues of stacked graphs, TouchWave also integrates hierarchical data within stacked graphs. We demonstrate TouchWave capabilities with two datasets—a music listening history and movie box office revenues—and discuss the implications for weaning other visualizations off mouse and keyboard.